Experimental and Numerical Study of Adding Bed Material in Swirling Gasification Using Palm Cake as Feedstock - Satawat khakkharo; Muhammad Arsal Cheema; Wasu Suksuwan; Arkom Palamanit; Mohd Faizal Mohideen Batcha; Makatar Wae-hayee (International Journal of Integrated Engineering, 2026)
Due to the energy demand for heat generation in the industrial sector, most rely on fossil fuels. However, with the limitations of decreasing resources and increasing prices, renewable energy presents an alternative to reduce dependence on fossil fuels by using biomass through the gasification process with a swirling fluidized bed gasifier (SFBG) to produce biomass gas that can be used further. This research aims to study the effect of syngas conversion by a fluidized bed gasifier, focusing on the impact of adding bed material during the conversion process, using palm oil decanter cake as biomass fuel to increase the efficiency of the syngas and to investigate the dynamic behavior of bed particles in the reactor. The research was divided into two parts: an experimental study and a numerical simulation. In the experimental study, two types of air inlet configurations were compared: updraft inlet and tangential/swirling inlet, under equivalence ratio (ER) values between 0.1 and 0.5, using silica sand as the bed material and a biomass feed rate of 3 kg/h. The CFD simulation used the Eulerian–Eulerian Multiphase Model to describe the gas and solid phase interactions inside the furnace. The simulation results showed that the addition of bed material improved mixing and temperature distribution inside the furnace, resulting in better syngas quality. The experimental comparison showed that the low heating value (LHV) of the syngas could reach an average maximum of 5.72 MJ/m³ in the ER range of 0.5 under the tangential inlet (TI) airflow configuration, indicating the important role of bed particle dynamics and air inlet design in future furnace performance.